Fibroma ossificante periférico: relato de caso - França, Diurianne Caroline Campos [UNESP]; Silva, Laís Soares; Marinho, Viviane Nogueira; Milanez Junior, João; Aburad, Arlindo Tadeu Teixeira; Aguiar, Sandra Maria Herondina Coelho Ávila de [UNESP] (My University, 2011)
The Peripheral ossifying fibroma is a reactive proliferative lesion, non neoplastic, slow growth, which can produce recurrence after removal. It´s etiology is uncertain, but is associated with local irritants, and is found mostly in the anterior maxilla. Clinically it is characterized by an asymptomatic increase in volume, which may, over time, facial asymmetry. The aim of this paper is to describe a case of peripheral ossifying fibroma in a patient 40, female, exophytic lesion in the jaw, unusual for its large dimensions and with a history of three recurrences, leading to facial asymmetry. She underwent surgery to remove the lesion along with the likely irritants, and the pathological diagnosis of peripheral ossifying fibroma. We conclude that it is fundamentally important for complete removal of the lesion to reduce the tendency to relapse, including the periosteum and the periodontal ligament, in addition to possible causes.

O Fibroma Ossificante Periférico é uma lesão proliferativa reacional, não neoplásica, de crescimento lento, que pode produzir recidiva após exérese. Sua etiologia é incerta, mas está associado a fatores irritantes locais, e é encontrado, na maioria das vezes, na região anterior de maxila. Clinicamente, caracteriza-se por um aumento volumétrico assintomático, que pode determinar, com o tempo, assimetria facial. O objetivo deste trabalho é descrever um caso de Fibroma Ossificante Periférico em paciente de 40 anos, sexo feminino, com lesão exofitica em maxila, atípico por suas grandes dimensões e com história de 3 recidivas, levando à assimetria facial. Foi submetida à cirurgia de remoção da lesão juntamente com os prováveis fatores irritantes, sendo o diagnóstico anatomopatológico de Fibroma Ossificante Periférico. Conclui-se que é de fundamental importância a remoção completa da lesão para minimizar a tendência à recidiva, incluindo o periósteo subjacente e o ligamento periodontal, além dos prováveis fatores causais.
Peripheral ossifying fibroma: case report
Keywords: Fibroma ossifying; Pathology oral; Recurrence; Fibroma ossificante; Patologia bucal; Recidiva